2021
DOI: 10.1002/hsr2.296
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness effects on lifestyle behavior and blood pressure: A randomized controlled trial

Abstract: Background and aims HTN affects nearly 50% of U.S. adults and is the leading modifiable cardiovascular risk factor. A healthy diet and exercise can improve BP control, but adherence to these interventions is low. We tested whether a multimodal mind–body program, Mindful Awareness Practices (MAP) could improve BP and lifestyle behaviors associated with HTN when compared to a Health Promotion Program (HPP). Methods Adults with BP >120/80 were randomized to MAP or HPP. Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…The app contains links to prerecorded meditations known as mindful awareness practices (MAPs), as well as training sessions and podcasts. It is widely available on all major mobile networks and the MAPs available in the app are supported by high-quality evidence that demonstrates they are effective in achieving the desired outcome (An et al, 2021;Galla et al, 2015;UCLA-MARC, 2022). The developers granted permission to use the app for this project and it was provided to participants at no cost.…”
Section: Innovation/interventionmentioning
confidence: 99%
“…The app contains links to prerecorded meditations known as mindful awareness practices (MAPs), as well as training sessions and podcasts. It is widely available on all major mobile networks and the MAPs available in the app are supported by high-quality evidence that demonstrates they are effective in achieving the desired outcome (An et al, 2021;Galla et al, 2015;UCLA-MARC, 2022). The developers granted permission to use the app for this project and it was provided to participants at no cost.…”
Section: Innovation/interventionmentioning
confidence: 99%
“…Nonetheless, a substantial portion of patients have poor compliance and mere health education is insufficient. Recent studies established the significant role mindfulness-based stress reduction (MBSR) interventions play in lifestyle optimization [ 20 , 21 ]. ISH guidelines emphasize that mindfulness practice should be assimilated into everyday life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While intervention in the control group was treatment as usual in three trials[41,59, 60, 63], wait-list in three trials[61, 62, 65] and active minutes to 2.5 hours each time. 5 to 45 minutes of home practice was required in 7 studies[21,41,59, 61, 62, 64, 66, 67]. Except for 4 studies, other researchers reported the quali cation of instructors of MBSR, including therapists trained for MBSR[62-64, 66], a licensed psychologist[61], an psychiatrist trained for MBCT[67], certi ed instructors[21] and nurses[60].…”
mentioning
confidence: 99%
“…5 to 45 minutes of home practice was required in 7 studies[21,41,59, 61, 62, 64, 66, 67]. Except for 4 studies, other researchers reported the quali cation of instructors of MBSR, including therapists trained for MBSR[62-64, 66], a licensed psychologist[61], an psychiatrist trained for MBCT[67], certi ed instructors[21] and nurses[60]. The follow-up time ranged from immediately post-intervention to 3 months after intervention (see Supplementary Material Table3).…”
mentioning
confidence: 99%
See 1 more Smart Citation